Pengembangan Kesehatan Tradisional Indonesia: Konsep, Strategi dan Tantangan - Siswanto, Siswanto (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2017)
Referred to ancient artifact and manuscript, Indonesian Traditional Medicine has been established and used by Indonesian people for maintaining health, treatment, and disease prevention. SWOT analysis has shown that Indonesia has the potencies and opportunities to develop Indonesian Traditional Medicine. The appropriate strategy to develop Indonesian Traditional Medicine is by conducting a 3P approach i.e. product, practice, and provider in a simultaneous way. The development of product is dealing with efficacy, safety and quality of product (modalities). The development of practice is dealing with the elaboration of the body of knowledge of Indonesian Traditional Medicine (Kestrindo) that can be used for formal education (Strata 1) in universities, to generate Kestrindo professionals, separated from conventional medicine. During the last three years, National Committee of Jamu Scientification has involved to elaborate and to establish the body of knowledge of Kestrindo. Kestrindo body of knowledge has the following building blocks, i.e. supporting pillars of biomedical science, philosophy of Indonesian origin, mechanism of action: physiogenesis (holistic), modalities of Indonesian origin (jamu, diet, massage, hypnotherapy, praying). As the philosophy of Kestrindo is holistic .i.e. paying attention a patient as holistic human being (body-mind-spirit), mixed methodology should be used. In this method, clinical outcome to be concerned is not only objective parameters (etic) but also subjective parameters (emic). In the future, it needs to finalize the concept of Kestrindo development for anticipation of global competitions and challenges and also to raise Indonesian nation integrity.